Macro-Financial Implications of the COVID-19 Pandemic - Utz, Robert; Feyen, Erik; Vazquez Ahued, Francisco; Nie, Owen; Moon, Jisung (World Bank, Washington, DC, 2020)
This paper examines the macro-financial implications of the COVID-19 pandemic. The pandemic represents a massive macro-economic demand and supply shock with significant adverse ramifications for global economic growth, employment, and poverty and demands an unprecedented response by national policy makers and international organizations. Prior to the outbreak of the pandemic, many economies already displayed increased macro-financial vulnerabilities in the form of high levels of debt of households, businesses, and the public sector, secular stagnation of economic growth, and an extended period of quantitative easing and low interest rates. The economic impact of the pandemic in the form of a global recession due to social distancing measures, losses of revenue and income for households, businesses, and the public sector, increased public spending to manage the health impacts, contain the pandemic, and protect vulnerable businesses, households, state-owned enterprises, and public entities adds significantly to pre-existing macro-financial vulnerabilities. Managing these vulnerabilities will be critical for a resilient recovery from the COVIC-19 pandemic, requiring a range of short- and medium term macro-financial policy measures.